Differential effects of methylphenidate and cocaine on GABA transmission in sensory thalamic nuclei. (7th January 2013) - Goitia, Belén; Raineri, Mariana; González, Laura E.; Rozas, José L.; Garcia‐Rill, Edgar; Bisagno, Verónica; Urbano, Francisco J.
Abstract Methylphenidate (MPH) is widely used to treat children and adolescents diagnosed with attention deficit/hyperactivity disorder. Although MPH shares mechanistic similarities to cocaine, its effects on GABAergic transmission in sensory thalamic nuclei are unknown. Our objective was to compare cocaine and MPH effects on GABAergic projections between thalamic reticular and ventrobasal (VB) nuclei. Mice (P18‐30) were subjected to binge‐like cocaine and MPH acute and sub‐chronic administrations. Cocaine and MPH enhanced hyperlocomotion, although sub‐chronic cocaine‐mediated effects were stronger than MPH effects. Cocaine and MPH sub‐chronic administration altered paired‐pulse and spontaneous GABAergic input differently. The effects of cocaine on evoked paired‐pulse GABA‐mediated currents changed from depression to facilitation with the duration of the protocols used, while MPH induced a constant increase throughout the administration protocols. Thalamic reticular nucleus GAD67 and VB CaV3.1 protein levels were measured using western blot to better understand their link to increased GABA release. Both proteins were increased by sub‐chronic administration of cocaine. MPH showed effects on GABAergic transmission that seems less disruptive than cocaine. Unique effects of cocaine on postsynaptic VB calcium currents might explain deleterious cocaine effects on sensory thalamic nuclei. These results suggest that cocaine and MPH produced distinct presynaptic alterations on GABAergic transmission.